D.H. Lawrence, James Joyce and the Impracticability of Home - Stefania Michelucci (Études Lawrenciennes)
In this paper I intend to discuss the concept of home and homelessness from an anthropological perspective. I will first analyze this concept in the short story “A Little Cloud” from Dubliners by James Joyce. In this story, the house/home becomes a prison which is almost impossible to escape from, undermining any dream. In the second part of my paper, I will compare this prison to the necessary, but problematic homelessness in Women in Love by D.H. Lawrence.